Everyday Memory in Healthy Aging: Porous but Not Distorted - Sejunaite, Karolina; Lanza, Claudia; Riepe, Matthias W. (Frontiers in Aging Neuroscience, 2019)
Most studies targeting age-association of memory functions report a decline in recognition hits and an increase in false alarms. The goal of the present study was to assess these findings in tasks with day-to-day relevance. We investigated healthy young (YA; age 26.90 ± 3.55 years) and old (OA; age 69.80 ± 5.85 years) adults. Participants were asked to watch six news and six commercials and complete a recognition task relating to the information presented in the videos. OA had a lower hit rate in both news and commercials compared to YA. However, the number of false alarms was the same in both age groups. Applying signal detection theory, we found age differences in discriminability for both news and commercials paradigm. The groups showed no differences in bias and both chose a liberal answering tendency. We interpret our finding as a result of complex recognition items in an ecologically valid task. Multi-feature items offer an advantage in correct rejection – it is enough to know that at least one feature of an item is false. This benefit does not extend to hits, where all features of an item need to be recognised. This indicates that recognition memory of naturalistic stimuli in OA is porous, but not distorted.